Loving God for Life: The Five Principles to Cultivate the Children’s Faith - Santoso, Magdalena Pranata; Joselito , Gutierrez; Alicia, Alicia (Aletheia Christian Educators Journal, 2026)
The greatest commandment and God's will for all Christians is to love God with all their heart, soul, mind, and strength. Especially amid the industrial revolution 4.0 where younger generations prefer to enjoy life and pursue personal satisfaction. To cultivate the children’s willingness to love God throughout their lives, Christian parents need to be guided by the Biblical principles. This study used a qualitative descriptive analysis research method based on a literature study that examined the process of developing faith in the lives of Bible heroes: Samuel, Moses, and Josiah who loved God all their lives, which is applied in Jewish education. The five models of children education, namely: (1) A Loving and Authentic Relationship Between Parents and Children from an Early Age; (2) The Father’s Role in Applying Spiritual Discipline; (3) Cultivates the Faith to Understand God’s Providence; (4) Cultivates the Children’s Faith in an Innovative, Holistic and Integrative Way; and (5) Cultivates the Children’s Faith Starting During Pregnancy. This method has been implemented in several Christian families for their children since they were toddlers. At age 18, parents reported on the character development of their children raised with a love-for-God education. This study demonstrates that applying biblical principles to the lives of the three Bible Heroes can help Christian parents raise their children to love God and develop good character.